The Relationship between Arm Muscle Strength and Tosser Volleyball Athletes at State Senior High School 13 Muko-Muko - Ahmad, Deliah (Journal Of Dehasen Educational Review, 2023)
This study aims to scientifically determine the relationship between arm muscle strength and passing skills in volleyball games. The formulation of the problem in this study is how big is the relationship between arm muscle strength and passing skills in the volleyball game of SMA Negeri 13 Muko-Muko? This research was conducted at the Volleyball Club of SMA Negeri 13 Muko-Muko. The research method used is the correlation method with product moment statistics, this research is objective or as it is with a sample of 30 athletes assisted by the Volleyball Club at SMA Negeri 13 Muko-Muko taken by total sampling technique. The results of the data Based on the results of research conducted at the Volleyball Club at SMA Negeri 13 Muko-Muko using the data normality test, homogeneity test, hypothesis test, it can be concluded as follows: 1) Test results and measurements of arm muscle strength through the push up test on skills passing in volleyball games is normally distributed, 2) Based on the results of tests that have been carried out that arm muscle strength has a significant relationship to passing skills in volleyball games.